A Chimeric Styrene Monooxygenase with Increased Efficiency in Asymmetric Biocatalytic Epoxidation. (23rd March 2018) - Corrado, Maria L.; Knaus, Tanja; Mutti, Francesco G.
Abstract: The styrene monooxygenase (SMO) system from Pseudomonas sp. consists of two enzymes (StyA and StyB). StyB catalyses the reduction of FAD at the expense of NADH. After the transfer of FADH2 from StyB to StyA, reaction with O2 generates FAD‐OOH, which is the epoxidising agent. The wastage of redox equivalents due to partial diffusive transfer of FADH2, the insolubility of recombinant StyB and the impossibility of expressing StyA and StyB in a 1:1 molar ratio reduce the catalytic efficiency of the natural system. Herein we present a chimeric SMO (Fus‐SMO) that was obtained by genetic fusion of StyA and StyB through a flexible linker. Thanks to a combination of: 1) balanced and improved expression levels of reductase and epoxidase units, and 2) intrinsically higher specific epoxidation activity of Fus‐SMO in some cases, Escherichia coli cells expressing Fus‐SMO possess about 50 % higher activity for the epoxidation of styrene derivatives than E. coli cells coexpressing StyA and StyB as discrete enzymes. The epoxidation activity of purified Fus‐SMO was up to three times higher than that of the two‐component StyA/StyB (1:1, molar ratio) system and up to 110 times higher than that of the natural fused SMO. Determination of coupling efficiency and study of the influence of O2 pressure were also performed. Finally, Fus‐SMO and formate dehydrogenase were coexpressed in E. coli and applied as a self‐sufficient biocatalytic system for epoxidation on greater than 500 mg scale. Abstract : Going in tandem is faster : A chimeric styrene monooxygenase (Fus‐SMO) was created through genetic fusion of bi‐enzymatic StyA and StyB. E. coli cells expressing Fus‐SMO showed improved epoxidation rates. The coupling efficiency and activity of purified Fus‐SMO were determined. Finally, E. coli cells coexpressing Fus‐SMO and formate dehydrogenase were applied as a self‐sufficient biocatalytic system for asymmetric epoxidation on preparative scale.